BURUNG MERAK SEBAGAI INSPIRASI PENCIPTAAN BUSANA MUSLIM - Vioridha Amaliah; Inty Nahari (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
The peacock as an inspiration for the creation of Muslim fashion is motivated by the visual beauty possessed by the peacock, which includes its body shape, patterns, and the distinctive color combinations of its feathers. However, the existence of this animal is currently threatened due to illegal hunting and habitat destruction, which have led to a decline in its population. This research is a creation-based study focusing on ready-to-wear clothing in the form of Muslim fashion with the peacock as the source of ideas. This study aims to: 1) Describe the process of creating evening Muslim fashion inspired by the peacock; 2) Determine the final outcome of the evening Muslim fashion inspired by the peacock; 3) Present the evening Muslim fashion inspired by the peacock. The method used in the creation of this work is Practice Led Research, which goes through four stages: pre-design, design, realization, and presentation of the work. The outcome of this creation consists of three pieces of evening Muslim fashion comprising 3 looks, namely men's wear, women's wear, and girls' wear, which interpret the visual characteristics of the peacock into clothing forms. The presentation of the works is carried out through visual documentation media supported by digital promotion to showcase the creation results.